(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The adapted meteorological elements in this study, wind speed, and air temperature were used in order to calculate the variation of wind speed with altitude, at Hillah city center during 2017. Wind speed and air temperature were observed for two different heights 10 m, 15 m. These observations have been done for 24 hours under various conditions of atmospheric stability. Richardson number was calculated as an indicator to estimate the conditions of stability, it should be noted that most of the observations were within unstable and neutral conditions. Roughness indicators such as roughness length and zero displacement length were used which determined from previous studies performed at the study area. In order to determine the horizontal wind speed, the observations were taken at deferent heights within the boundary layer by using the logarithmic wind profile which involves the indicator of stability and frictional wind speed. In addition, the correction coefficient of the Richardson number was calculated through stable and unstable conditions. Besides, the horizontal wind speed was calculated and then compared with the practical values.